Pear Deck Utilization to Improve Learners' Motivation and Emotional Engagement - Margaretta, Iga Shevy; Rohmah, Zuliati; Hamamah; Muttaqin, Syariful (NOBEL: Journal of Literature and Language Teaching, 2024)
Along with the rapid development of technology, many educational platforms nowadays are used to support teaching and learning processes. Among these platforms is Pear Deck. It is an interactive platform that offers benefits to effectively increase students’ motivation and emotional engagement. This study aims to identify students’ motivation and emotional engagement in English lessons by utilizing Pear Deck. This case study revealed that the students feel emotions before the sessions start, all linked to their past experiences (retrospective outcomes). Fear, happiness, and excitement are the emotions the students feel at the beginning of the sessions, and they turn out to be enjoyable and happy at the end of the session. The emotions that the students feel during the sessions can potentially lead to the prospective outcomes of the students, which are success in their future endeavors. Additionally, the choice of suitable materials that will be delivered to the students must be considered by the teachers or educators to encourage and motivate students and uplift students’ emotional engagement with the lesson.